1986
DOI: 10.1128/jvi.57.2.481-489.1986
|View full text |Cite
|
Sign up to set email alerts
|

Human parainfluenza type 3 virus hemagglutinin-neuraminidase glycoprotein: nucleotide sequence of mRNA and limited amino acid sequence of the purified protein

Abstract: The nucleotide sequence of mRNA for the hemagglutinin-neuraminidase (HN) protein of human parainfluenza type 3 virus obtained from the corresponding cDNA clone had a single long open reading frame encoding a putative protein of 64,254 daltons consisting of 572 amino acids. The deduced protein sequence was confirmed by limited N-terminal amino acid microsequencing of CNBr cleavage fragments of native HN that was purified by immunoprecipitation. The HN protein is moderately hydrophobic and has four potential sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(35 citation statements)
references
References 49 publications
0
35
0
Order By: Relevance
“…Phylogenetic group C remained as the most dynamic and widespread group worldwide (Almajhdi, 2015;Mao et al, 2012). Nucleotide sequences analyzed in comparison with different international strains demonstrated an association with some Chinese strains (C3a) (Mao et al, 2012) and Saudi Arabia strains (C1b and C5) (Almajhdi, 2015;Almajhdi et al, 2012), whereas no association with strains from America (Elango et al, 1986;van Wyke Coelingh et al, 1988), India (unpublished) or Australia (Lawrence et al, 2004;van Wyke Coelingh et al, 1988) was observed. In addition, a new lineage (C1c) was first described in the present study.…”
Section: Discussionmentioning
confidence: 89%
“…Phylogenetic group C remained as the most dynamic and widespread group worldwide (Almajhdi, 2015;Mao et al, 2012). Nucleotide sequences analyzed in comparison with different international strains demonstrated an association with some Chinese strains (C3a) (Mao et al, 2012) and Saudi Arabia strains (C1b and C5) (Almajhdi, 2015;Almajhdi et al, 2012), whereas no association with strains from America (Elango et al, 1986;van Wyke Coelingh et al, 1988), India (unpublished) or Australia (Lawrence et al, 2004;van Wyke Coelingh et al, 1988) was observed. In addition, a new lineage (C1c) was first described in the present study.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, infectivity of this chimeric virus would depend on incorporation of EBOV GP, which directs both attachment and fusion, into the particle. EBOV GP is a type I transmembrane protein that has an unusually short C-terminal cytoplasmic tail (CT) KFVF (Sanchez et al, 1993) that bears no sequence similarity to the much longer 23 amino acid C-terminal CT of the type I HPIV3 F protein (Spriggs et al, 1986), or the 31 amino acid N-terminal CT of the type II HPIV3 HN protein (Elango et al, 1986). The efficiency of incorporation of a foreign glycoprotein into a virus particle can be influenced by its CT, such that replacement of the foreign CT with that from an endogenous glycoprotein can increase incorporation (Tao et al, 2000).…”
Section: Functional Replacement Of the Hpiv3 Hn And F Proteins By Ebomentioning
confidence: 99%
“…Steric hindrance between the cytoplasmic tail of these proteins and the capsids of the budding virus particles is one likely mechanism by which proteins are actively excluded from lentiviruses (Henriksson et al, 1999). Although we can not rule out the possibility that HPIV3 Env are actively excluded from lentiviruses, it seems unlikely that steric hindrance plays a role since both HPIV3-HN and -F have short cytoplasmic domains (31 and 23 amino acids, respectively (Elango et al, 1986;Spriggs et al, 1986)), and envelope proteins with naturally short cytoplasmic tails such as MuLV Env, and envelope proteins from HIV-2 and SIV with long cytoplasmic tails that have been truncated, have been shown to be efficiently incorporated into lentiviral particles (Freed and Martin, 1995;Zingler and Littman, 1993).…”
Section: Discussionmentioning
confidence: 88%